ProQuest dissertations & theses global (ProQuest, 2014)
ProQuest Dissertations and Theses — Full text is the world's most comprehensive collection of dissertations and theses. The official digital dissertations archive for the Library of Congress and the database of record for graduate research. PQDT — Full Text includes millions of searchable citations to dissertation and theses from around the world from 1861 to the present day together with over a million full text dissertations that are available for download in PDF format. Over 2.1 million titles are available for purchase as printed copies. The database offers full text for most of the dissertations added since 1997 and strong retrospective full text coverage for older graduate works. More than 70,000 new full text dissertations and theses are added to the database each year through dissertations publishing partnerships with 700 leading academic institutions worldwide and collaborative retrospective digitization of dissertations through UMI's Digital Archiving and Access Program. Full Text dissertations are archived as submitted by the degree-granting institution. Some will be native PDF, some PDF image. Each dissertation published since July 1980 includes a 350-word abstract written by the author. Master's theses published since 1988 include 150-word abstracts. Simple bibliographic citations are available for dissertations dating from 1637. Where available, PQDT — Full Text provides 24-page previews of dissertations and theses. (Cited description: ProQuest LLC)